2011
DOI: 10.4314/bajopas.v2i2.63788
|View full text |Cite
|
Sign up to set email alerts
|

<i>Helicobacter pylori</i>: the causative agent of peptic ulcer

Abstract: This review examines Helicobacter pylori as an organism and as the causative agent of peptic ulcers. The review also examined the classification of ulcers, how the bacterium produces the ulcer, some of the virulence factors possessed by the organism, its metabolism and growth requirements. The incidence and prevalence of peptic ulcers were originally believed to have resulted from some factors such as stress, eating spicy food, long term use of nonsteroidal anti-inflammatory agents (NSAIDs), like aspirin and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…According to HIES (2016), gastric ulcers among urban dwellers (20.3%) are most common; in the present study, gastric ulcers were found linked to both safe (piped water into dwelling and yard) and unsafe (river and pond) sources (Table 3). Nonetheless, the increased prevalence of stomach ulcers in surveyed communities might result from an irregular diet, drinking less water, and stress-related factors (Shamsuddeen et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…According to HIES (2016), gastric ulcers among urban dwellers (20.3%) are most common; in the present study, gastric ulcers were found linked to both safe (piped water into dwelling and yard) and unsafe (river and pond) sources (Table 3). Nonetheless, the increased prevalence of stomach ulcers in surveyed communities might result from an irregular diet, drinking less water, and stress-related factors (Shamsuddeen et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…It was identified in 1982 (1). It has been established that H. pylori infection is a major cause of chronic gastritis and peptic ulcer disease (2). H. pylori is the causative agent for acute and chronic gastritis and gastric lymphoma.…”
Section: Introductionmentioning
confidence: 99%